Bab Al-Halba Tower Between Repeal and Excavation - AL- Tamimi, Najat Ali (Al-Adab Journal, 2021)
For a century, the base of Bab Al-Halba tower remained lying under the excesses, rubble and wheel remnants, the tower was subjected to vandalism, weakness and deliberate destruction by the Ottoman government after losing the First World war and it turned into a trace after it was visible.After that, the researchers started to argue about the nature of this material, the controversy has continued about the nature of the voussoir's material from which the entrance of the arch of Bab Al- Halba Tower was constructed, it is one of the gates of the eastern wall of Baghdad, naming as that according to the land in where Bab Al - Halba was built, this land was a race track or playground for the Chaugan sport at that time before building the tower (Table No.1).Bab Al- Halba was known locally as Bab Al- Talsim,(·) this naming came late, relatively to the decoration of the bricks that adorn the spandrels of its entrance arch (Table No.2), The people at the time considered it as a talisman to protect the city from the evils of enemies , Ibn al-jawzi(part 9, p81), The tower was also known as Baroud Khana(·) ,relatively to the gunpowder in which it was stored , also known to the residents of Baghdad as Bab Al –Sheikh , for it is near to the shrine of Sheikh Abdul Qadir Al- Gilani, and the tower was translated by Guy le strange as the White Gate, (ak kapi) , However, the latter did not explain the reasons of the naming, Which is most likely a nickname given to places that maintain their peace in times of wars and invasions.The reasons of this controversy attributed to several major things including:The tower is un prominent as it was demolished on 11 of March 1917 at the end of First World War, when it was blown up by Ottoman troops at the time of their withdrawal from Baghdad; while the British troops were advancing in order to undermine the opportunity and prevent using the ammunition that deposited inside the tower, which it was set up for defending the wall, that led to scatter the tower into fragments and fall into piles of stones, and from that time till now the historical sources or archaeological discoveries have not mentioned yet the place of the tower or any indication of the structural foundations of it; that what we going to discuss after investigating between the folds of documents in the department of documentation of the state board of antiquities and heritage, and as a result no trace remains except what was discovered by pure coincidence , so it has not been highlighted during a period of nearly a century , as well as the historical sources (Non- specialized) did not mention the structural details of the arch in particular beside that , the identification of the type of structural details which have been used in making the voussoirs , whether they are joggled or were made as an interlocked for decorative purposes , in addition to the outstanding archaeological buildings in Baghdad and the nearby ones that date back to close periods of time from the construction of the tower in particular and the antiquity of Iraq in general from the outstanding ones or those that have been removed for great reasons did not provide us with examples for the type of voussoirs. What we get exclusively in this site are all that we have mentioned before of reasons that did not help the researchers in the field of architectural decorations of the bricks or even help those who searched in the buildings façades in making comparison between those voussoirs and the opinion of the researcher towards the nature of the building materials of the voussoirs, (al-Tamimi, 2014, footnote5, p.44). Therefore, most of the researchers including the owner of the research have relied on researchers who preceded us to know and seek the nature of voussoirs whether they are joggled or just architectural decorations that were carried out perfectly on the form of joggled; so, we present this study to stand on this problem and to give a new opinion, beside to look for the reasons of discovering the base of the tower which has not been published yet. The nature of the research necessitated that it be organized into three topics:-The first topic: A brief history of eastern walls of Baghdad between revocation, maintenance and documentation.-The second topic: An exploration of the tower and the excavation and restoration works.-The third topic: Methods of making joggled voussoirs, as well as the results of the research, an English summary and list of research sources and references. -al- talisman ,for more See - Al-Shahristani, Imam Abi Al-Fateh Muhammad bin Abdul Karim, (died 548 A.H) Al-MILAL WA AL-NAHL , investigated and commented by Ahmed Fahmy Mohamed, library of science books ,Beirut,2009,p2,p349; Ibn Khaldun, Abd al-Rahman, “Introduction” Kitab al-Ibr and the Diwan of the almubtada wa al khubar in the Days of the Arabs, Ajam, and Berbers and their Contemporary from the Great Sultan, Al-Muthanna Library, Baghdad, without history, vol.1, p. 496-498; Al-Tahanawi, Muhammad Ali, Encyclopedia of Idioms and Sciences, Presentation, Supervision and Participation by: Dr.George Zenari ,Lebanon library,Lebanon,1996,p1,p57. - Gunpowder is a store of gunpowder, which is a Turkish term. Consulting by prof. Dr. Imad Al-Din Salloum Al-Abbasi Specialist in oriental ​​-Farsi languages, College of Languages, on 3/12/2017 AD